PERANCANGAAN MESIN PENGERING MINYAK KAPASITAS 10 KG - Sir Anderson (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2022)
Repeated heating of paml oil has a greater effect to produce high levels of trans fat. The excess consumsion of food contained trans fat is couse of diabetes and coronary heart diseas. The oil spinner machine of 10 kg capacity are proposed to overide this problem because it is able to throw the oil particles out from the fried food caused by centrifugal force. The drying area is a 50 cm long tube having diameter of 40 cm which is driven by an electric motor single-phase 1 Hp 1400 rpm. In order to increase the speed of the drying tube into 2800 rpm, a 6 inch diameter pulley attached to the motor shaft while a 3 inch is mounted on a 10 cm diameter drying tube shaft. The two pulleys are connected by means of an open belt drive with a length of 60 inch and 187,480 the contact angle.